PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MODERASI : (Studi Penelitian Pada Tenaga Kependidikan STIESIA Surabaya) - Nur Cahyono, Gunawan (Jurnal Administrasi Publik, 2024)
The Influence Job Satisfaction to Employee Performance With Organization Citizenship Behavior as Moderation Variable (Research Study on Education Employee STIESIA Surabaya). Employees have various kinds of needs that they want to fulfill through various ways, one of which is by working, the efforts made by employees by working are aimed at fulfilling needs, in other words to be able to live a decent human life based on their human nature, employees have various needs. which must be fulfilled. The theoretical study used in this research is the theory of job satisfaction, organizational citizenship behavior and employee performance, and the research method used in this research uses Path Analysis, influence between variables. The research results show the following results: Job Satisfaction (X) has a positive and significant influence on Organizational Citizenship Behavior (Z) in STIESIA Surabaya educational staff employees. This can be shown by the t-statistic value (18.179) >1.96 with a significance level of 0.000. Job Satisfaction (X) has a significant positive influence on Employee Performance (Y) of STIESIA Surabaya education staff. This can be shown by the t-statistic value (2.944) >1.96 with a significance level of 0.003. Organizational Citizenship Behavior (Z) has a significant positive influence on Employee Performance (Y) of STIESIA Surabaya education staff employees. This is shown by the t-statistic number (2.185) >1.96 and a significance level of 0.029